Endoscopic gastric mucosal atrophy distinguishes the characteristics of superficial esophagogastric junction adenocarcinoma. (20th April 2017) - Uedo, Noriya; Yoshio, Toshiyuki; Yoshinaga, Shigetaka; Takeuchi, Manabu; Hatta, Waku; Yano, Tomonori; Tanuma, Tokuma; Goto, Osamu; Takahashi, Akiko; Tong, Daniel; Lee, Yeong Yeh; Nakayama, Yoshiko; et al.
Abstract : Background and Aim: Western studies have suggested two distinct etiologies of esophagogastric junction (EGJ) cancer: Helicobacter pylori ‐associated atrophic gastritis and non‐atrophic gastric mucosa resembling esophageal adenocarcinoma. The present study investigated whether endoscopic gastric mucosal atrophy can distinguish between these two types of EGJ adenocarcinoma. Methods: Data were collected from patients with Siewert type II, T1 EGJ adenocarcinoma who underwent endoscopic or surgical resection at eight Japanese institutions in 2010–2015. Clinicopathological characteristics of EGJ cancers with and without endoscopic gastric mucosal atrophy were compared. EGJ was defined as the lower end of the palisade vein and/or the top of the gastric folds. Results: Of the 229 patients identified, 161 had endoscopic gastric mucosal atrophy and 68 did not. The latter group was younger (64 vs 70 years, P = 0.000); had a higher proportion of patients negative for H. pylori (90% vs 47%, P < 0.0001); and had higher rates of gastroesophageal reflux disease symptoms (43% vs 12%, P = 0.017), mucosal breaks (25% vs 15%, P = 0.009), Barrett's esophagus (BE, 78% vs 42%, P < 0.0001), and tumors above the EGJ (81% vs 19%, P < 0.0001) and on the upper‐right side (74% vs 38%, P < 0.0001) than the former group. Multivariate analysis showed that H. pylori positivity (odds ratio [OR] = 13.0, P < 0.001), long‐segment BE (OR = 0.025, P = 0.033), and longitudinal (OR = 8.6, P = 0.001) and circumferential (OR = 4.7, P = 0.006) tumor locations were independently associated with gastric mucosal atrophy. Conclusion: Two distinct types of EGJ cancer were identified, with and without endoscopic gastric mucosal atrophy. These types were associated with different tumor locations.